Thyroid Cancer-Associated Mitochondrial DNA Mutation G3842A Promotes Tumorigenicity via ROS-Mediated ERK1/2 Activation. (15th March 2022) - Chen, Sixi; Bao, Xinzhu; Chen, Hongzhi; Jia, Manli; Li, Wen; Zhang, Luyi; Fan, Runxiao; Fang, Hezhi; Jin, Liqin
Abstract : Mitochondrial DNA (mtDNA) mutations have been identified in various human cancers, including thyroid cancer. However, the relationship between mtDNA and thyroid cancer remains unclear. Previous studies by others and us strongly suggested that mtDNA mutations in complex I may participate in thyroid cancer processes according to sequencing results of thyroid cancer tissue, although the associated pathogenic processes remain unknown. Here, to investigate whether mtDNA mutations contribute to thyroid cancer, we reanalyzed our sequencing results and characterized thyroid cancer-associated mutations in the mitochondrial complex. The results identified the highest mutation frequencies in nicotinamide adenine dinucleotide hydride (NADH) dehydrogenase subunit 4 gene ( ND4 ) and cytochrome c oxidase subunit 1 gene ( COI ), which also harbored the highest rates of G > A substitutions, with most of the mutations resulting in changes in the polarity of amino acids. We then established cybrids containing the G3842A mutation identified in papillary thyroid carcinoma, which revealed it as a mutation in NADH dehydrogenase subunit 1 gene ( ND1 ) and is previously reported in follicular thyroid carcinoma, thereby suggesting a possibly pathogenic role in thyroid carcinoma. Additionally, we found that the G3842A mutation accelerates tumorigenicity and decreases the abundance and activity of mitochondrial complex I, the oxygen consumption rate, and adenosine triphosphate levels. By contrast, the levels of reactive oxygen species (ROS) were increased to activate extracellular signal-regulated kinase (ERK1/2) signaling, which contributed to tumorigenicity. These findings suggest for the first time that mtDNA mutations help drive tumor development and that G3842A may represent a new risk factor for thyroid cancer. Furthermore, our findings indicate that drugs targeting ROS and ERK1/2 may serve as a viable therapeutic strategy for thyroid cancer.